The Role of TQM, Innovation and Internationalization Strategies on the Financial Sustainability of Higher Education Institutions - Antunes, Marina Godinho (2019)
This research aims to study the role that Total Quality Management (TQM), innovation and internationalization strategies may have on the financial sustainability of Portuguese higher education institutions (HEIs), through a literature review that supports the presentation of a research model proposed by the authors. This research is justified by the observation of a reality still relatively little studied at the level of higher education institutions, not only in Portugal, but also in other countries, particularly regarding the prospect of financial sustainability, in line with the growing relevance that quality and innovation strategies have been taken in these institutions. Undoubtedly, also the perspective of internationalization is something that currently HEIs cannot ignore at all if they want to be considered competitive and innovative in the academic world. Increasingly, international rankings that follow strict criteria for assessing the quality, innovation and scientific research of HEIs have assumed paramount importance in the analysis of the performance of these institutions. Education, and particularly education provided in HEIs, is a resource of enormous value for the development of any society [1-2]. The literature has demonstrated that TQM practices are a powerful tool for improving organizational learning and increasing competitive advantage [3-4]. In addition to the importance of the quality of education in HEIS, emphasized through the implementation of TQM practices, this will be more easily achieved by considering organizational learning and organizational innovation to provide better services, not only to students, but also to the whole society. Despite the importance identified in the relationship between these different dimensions, the literature has also highlighted the fact that educational institutions, despite the growing recognition of their importance, are falling short of other organizations, concerning the implementation of practices leading to a culture of total quality [5]. Regarding the methodology, the data will be obtained through the application of a questionnaire prepared by the authors, to evaluate the different dimensions of the proposed research model. The sample will be for convenience, consisting of about 200 emails from members of the management boards of Portuguese universities and polytechnics. In the treatment of quantitative data, the use of the multiple linear regression model is considered, to investigate the possible relationships between the different dimensions incorporated in the model. According to Hair et al. [6], it is a practical statistical tool that examines the linkages between a set of independent variables with a dependent variable. In this way, we consider this statistical method the most adequate for the development of our research. In terms of discussion of results, it is intended to characterize the various dimensions of the TQM, as well as the strategies of innovation and internationalization in the institutions of university and polytechnic higher education in Portugal, seeking to understand their role and possible relations with the financial sustainability of these institutions.